Agricultural applications - Kempken, Frank (The Mycota, A Comprehensive Treatise on Fungi as Experimental Systems for Basic and Applied Research, 2013)
This volume covers the high relevance of fungi for agriculture. It is a completely updated and revised second edition with fourteen excellent chapters by leading scientists in their fields and offers a comprehensive review of the latest achievements and developments. Topics include: Food and fodder; fungal secondary metabolites and detoxification; biology, disease control and management; symbiontic fungi and mycorrhiza; and phytopathogenicity.